THE EFFECT OF PREGNANT WOMEN CLASSES ON THE IMPROVEMENT OF KNOWLEDGE OF PREGNANT WOMEN IN SEGERAN KIDUL VILLAGE - Cucu Nurmala (JURNAL KESEHATAN INDRA HUSADA, 2021)
Currently, maternal and child health education is generally still carried out through counseling, individual consultations or on a case-by-case basis, which is given when a mother is checking her womb or during posyandu activities. To overcome these various weaknesses, a learning method for pregnant women was developed.This activity is designed face-to-face by discussing the material in the MCH Handbook accompanied by discussions and sharing of experiences between pregnant women/husbands/families and health workers. This study group activity is named the class of pregnant women as a form of preventive and promotive efforts based on the Regulation of the Minister of Health No. 97 of 2014.Mothers who have attended the Pregnant Women Class are expected to have a change in behavior or an increase in knowledge so that they are aware of the importance of coming to health services. Research Purposes: This is to determine the effect of the class of pregnant women on increasing the knowledge of pregnant women in Segeran Kidul villages. Research Methods: The type of research used is analytical research, with a pre-experimental design, with a one group Pre-Post Design approach. In this study, researchers used a total sampling of 32 people. Data collection was in the form of a questionnaire that was filled in by pregnant women before and after the implementation of the class for pregnant women. Univariate and bivariate data analysis techniques used paried t-test.Research Results: The results showed that the mean score of pre-test knowledge was 16.88, and post-test knowledge increased by an average of 21.59, which means that there was an increase of 4.719. The results of statistical calculations obtained the t value of -8.354 and the p value of 0.000 so that the p value<0.05 means that there is an influence of the class of pregnant women on the increase in knowledge.